Promoting language learning skills to young ESL learners / D. Rohayu Mohd Yunos, Sharifah Amani Syed Abdul Rahman and Normah Ismail - Mohd Yunos, D. Rohayu; Syed Abdul Rahman, Sharifah Amani; Ismail, Normah (2011)
One of the most frequent problems ESL (English as a Second Language) teachers face is how to promote English among young ESL learners. One viable way is to transform English from a school subject into a medium for authentic communication. This transformation encourages young learners to use the language not only for meaningful exchanges, but also as a tool for self-expression and creativity. When they are able to use language in a creative and original way, they become involve in the process of communication and language production. The purpose of this study is to explore how language games can be utilized to promote language learning among a group of Primary Six students. The students participated in a language camp which provided them with the opportunity to use written English in a useful and creative way. Feedback from the students showed that they felt that the activities carried out during the camp were meaningful and enjoyable. The paper ends with some ideas how teachers can use such language programs to promote other language skills or work with different groups of learners.